On the role of technology in political communication research - Dylko, Ivan B. (Javnost (Ljubljana), 2013)
This article reviews multi-disciplinary body of research to develop a model ofhow technology impacts communication processes at various stages. The model,which includes psychological and technological factors, is argued to represent a more useful framework for political communication- effects theory building than frameworks offered by either social constructivist or technological determinism perspectives. The article also argues for a greater inclusion of technology into existing political communication theorising. Several future research directions further developing this argument are described.
Keywords: communication; komuniciranje; politične komunikacije; technology; tehnologija; tehnološki razvoj